Aspirin Improves Nonalcoholic Fatty Liver Disease and Atherosclerosis through Regulation of the PPARδ-AMPK-PGC-1α Pathway in Dyslipidemic Conditions. (19th March 2020) - Han, Yoon-Mi; Lee, Yong-Jik; Jang, Yoo-Na; Kim, Hyun-Min; Seo, Hong Seog; Jung, Tae Woo; Jeong, Ji Hoon
Abstract : This study is aimed at elucidating how aspirin could systemically and simultaneously normalize nonalcoholic fatty liver disease (NAFLD) and atherosclerosis through both in vitro and in vivo studies in hyperlipidemic conditions. We evaluated the effects and mechanism of aspirin on the levels of various biomarkers related to NAFLD, atherosclerosis, and oxidative phosphorylation in cells and animals of hyperlipidemic conditions. The protein levels of biomarkers (PPAR δ, AMPK, and PGC-1 α ) involved in oxidative phosphorylation in both the vascular endothelial and liver cells were elevated by the aspirin in hyperlipidemic condition. Also in the stimulation pathway of oxidative phosphorylation by aspirin, PPAR δ was a superior regulator than AMPK and PGC-1 α in HepG2 cells. In the vascular endothelial cells, the phosphorylated endothelial nitric oxide synthase level was increased by the treatment. The protein levels of biomarkers related to lipid synthesis were decreased by the treatment in the liver cells. In rabbits administered with cholesterol diet, the levels of triglyceride, HDL-cholesterol, and alanine amino transferase in serums were ameliorated by the aspirin treatment, the levels of ATP and TNF α were increased or decreased, respectively, by the aspirin in liver and aorta tissues, and mannose receptor and C-C chemokine receptor type 2 levels were increased or decreased by the aspirin in spleen, respectively. The elevated levels of macrophage antigen, angiotensin II type1 receptor, and lipid accumulation were decreased in both the liver and aorta tissues in the aspirin-treated group. In conclusion, aspirin can systemically and simultaneously ameliorate NAFLD and atherosclerosis by inhibiting lipid biosynthesis and inflammation and by elevating catabolic metabolism through the activation of the PPAR δ -AMPK-PGC-1 α pathway. Furthermore, aspirin may normalize atherosclerosis and NAFLD by modulating the mannose receptor and CCR2 in macrophages.